Evaluation of labor and childbirth care by nurse-midwives in Brazilian private hospitals: results of a quality improvement project - Fabrine C. Souza; Rosa Maria Soares Madeira Domingues; Jacqueline Alves Torres; Maysa Luduvice Gomes; Maria do Carmo Leal (BMC, 2023)
Plain Language Summary Brazil has a high rate of cesarean sections with low participation of nurse-midwives in childbirth care. Nurse-midwife care is associated with less use of interventions, lower proportions of cesarean sections and greater women's satisfaction. In 2015, a quality improvement project, called the "Adequate Childbirth Project" (Projeto Parto Adequado, PPA), was implemented in Brazilian private hospitals to reduce unnecessary cesarean sections. One of its components is the expansion of nurse-midwives in labor and childbirth care. In this study, we evaluated the results of PPA on childbirth care by nurse-midwives. Data were collected in 12 hospitals with interviews with 4798 women. Women assisted in the PPA model of care had a higher proportion of labor and vaginal birth, but there was no increase in the proportion of women assisted by nurse-midwives, neither during labor nor vaginal birth. The use of recommended practices was adequate, except for the use of epidural analgesia, with greater use of some recommended practices in women assisted by nurse-midwives compared to those seen only by doctors. However, we observed excessive use of non-recommended practices during labor, both by doctors and nurses. We can conclude that there was an increase in the proportion of women with labor and vaginal birth in the PPA model of care and a greater use of recommended practices in women assisted by nurse-midwives, but without an increase in the proportion of women assisted by nurses. The expansion of nurse-midwives' participation in childbirth care and the reduction of non-recommended practices therefore continue to be challenges.